CD40 agonistic monoclonal antibody APX005M (sotigalimab) and chemotherapy, with or without nivolumab, for the treatment of metastatic pancreatic adenocarcinoma: an open-label, multicentre, phase 1b study. Issue 1 (January 2021) - O'Hara, Mark H; O'Reilly, Eileen M; Varadhachary, Gauri; Wolff, Robert A; Wainberg, Zev A; Ko, Andrew H; Fisher, George; Rahma, Osama; Lyman, Jaclyn P; Cabanski, Christopher R; Mick, Rosemarie; Gherardini, Pier Federico; et al.
Summary: Background: Standard chemotherapy remains inadequate in metastatic pancreatic adenocarcinoma. Combining an agonistic CD40 monoclonal antibody with chemotherapy induces T-cell-dependent tumour regression in mice and improves survival. In this study, we aimed to evaluate the safety of combining APX005M (sotigalimab) with gemcitabine plus nab-paclitaxel, with and without nivolumab, in patients with pancreatic adenocarcinoma to establish the recommended phase 2 dose. Methods: This non-randomised, open-label, multicentre, four-cohort, phase 1b study was done at seven academic hospitals in the USA. Eligible patients were adults aged 18 years and older with untreated metastatic pancreatic adenocarcinoma, Eastern Cooperative Oncology Group performance status score of 0–1, and measurable disease by Response Evaluation Criteria in Solid Tumors version 1.1. All patients were treated with 1000 mg/m 2 intravenous gemcitabine and 125 mg/m 2 intravenous nab-paclitaxel. Patients received 0·1 mg/kg intravenous APX005M in cohorts B1 and C1 and 0·3 mg/kg in cohorts B2 and C2. In cohorts C1 and C2, patients also received 240 mg intravenous nivolumab. Primary endpoints comprised incidence of adverse events in all patients who received at least one dose of any study drug, incidence of dose-limiting toxicities (DLTs) in all patients who had a DLT or received at least two doses of gemcitabine plus nab-paclitaxel and one dose of APX005M during cycle 1, and establishing the recommended phase 2 dose of intravenous APX005M. Objective response rate in the DLT-evaluable population was a key secondary endpoint. This trial (PRINCE, PICI0002) is registered with ClinicalTrials.gov, NCT03214250 and is ongoing. Findings: Between Aug 22, 2017, and July 10, 2018, of 42 patients screened, 30 patients were enrolled and received at least one dose of any study drug; 24 were DLT-evaluable with median follow-up 17·8 months (IQR 16·0–19·4; cohort B1 22·0 months [21·4–22·7], cohort B2 18·2 months [17·0–18·9], cohort C1 17·9 months [14·3–19·7], cohort C2 15·9 months [12·7–16·1]). Two DLTs, both febrile neutropenia, were observed, occurring in one patient each for cohorts B2 (grade 3) and C1 (grade 4). The most common grade 3–4 treatment-related adverse events were lymphocyte count decreased (20 [67%]; five in B1, seven in B2, four in C1, four in C2), anaemia (11 [37%]; two in B1, four in B2, four in C1, one in C2), and neutrophil count decreased (nine [30%]; three in B1, three in B2, one in C1, two in C2). 14 (47%) of 30 patients (four each in B1, B2, C1; two in C2) had a treatment-related serious adverse event. The most common serious adverse event was pyrexia (six [20%] of 30; one in B2, three in C1, two in C2). There were two chemotherapy-related deaths due to adverse events: one sepsis in B1 and one septic shock in C1. The recommended phase 2 dose of APX005M was 0·3 mg/kg. Responses were observed in 14 (58%) of 24 DLT-evaluable patients (four each in B1, C1, C2; two in B2). Interpretation: APX005M and gemcitabine plus nab-paclitaxel, with or without nivolumab, is tolerable in metastatic pancreatic adenocarcinoma and shows clinical activity. If confirmed in later phase trials, this treatment regimen could replace chemotherapy-only standard of care in this population. Funding: Parker Institute for Cancer Immunotherapy, Cancer Research Institute, and Bristol Myers Squibb.